Optical modulator based on propagating surface plasmon coupled fluorescent thin film: proof-of-concept studies. (21st April 2017) - Cao, Shuo-Hui; Wang, Zheng-Chuang; Weng, Yu-Hua; Xie, Kai-Xin; Chen, Min; Zhai, Yan-Yun; Li, Yao-Qun
Abstract: We demonstrate that the propagating surface plasmon coupled fluorescent thin film can be utilized as a fluorescence modulator to mimic multiple representative Boolean logic operations. Surface plasmon mediated fluorescence presents characteristic properties including directional and polarized emission, which hold the feasibility in creating a universal optical modulator. In this work, through constructing the thin layer with the specific thickness, surface plasmon mediated fluorescence can be modulated with an ON-OFF ratio by more than 5-fold, under a series of coupling configurations.